Aerosol optical properties calculated from size distributions, filter samples and absorption photometer data at Dome C, Antarctica, and their relationships with seasonal cycles of sources - A. Virkkula; A. Virkkula; H. Grythe; J. Backman; T. Petäjä; M. Busetto; C. Lanconelli; C. Lanconelli; A. Lupi; S. Becagli; S. Becagli; R. Traversi; et al. (Atmospheric Chemistry and Physics, 2022)
Optical properties of surface aerosols at Dome C, Antarctica, in 2007–2013 and their potential source areas are presented. Scattering coefficients (σsp) were calculated from measured particle number size distributions with a Mie code and from filter samples using mass scattering efficiencies. Absorption coefficients (σap) were determined with a three-wavelength Particle Soot Absorption Photometer (PSAP) and corrected for scattering by using two different algorithms. The scattering coefficients were also compared with σsp measured with a nephelometer at the South Pole Station (SPO). The minimum σap was observed in the austral autumn and the maximum in the austral spring, similar to other Antarctic sites. The darkest aerosol, i.e., the lowest single-scattering albedo ωo≈0.91, was observed in September and October and the highest ωo≈0.99 in February and March. The uncertainty of the absorption Ångström exponent αap is high. The lowest αap monthly medians were observed in March and the highest in August–October. The equivalent black carbon (eBC) mass concentrations were compared with eBC measured at three other Antarctic sites: the SPO and two coastal sites, Neumayer and Syowa. The maximum monthly median eBC concentrations are almost the same (∼3±1<svg:svg xmlns:svg="http://www.w3.org/2000/svg" width="36pt" height="10pt" class="svg-formula" dspmath="mathimg" md5hash="6442f66d659a0105dc28ae4509c7c5b1"><svg:image xmlns:xlink="http://www.w3.org/1999/xlink" xlink:href="acp-22-5033-2022-ie00001.svg" width="36pt" height="10pt" src="acp-22-5033-2022-ie00001.png"/></svg:svg> ng m−3) at all these sites in October–November. This suggests that there is no significant difference in eBC concentrations between the coastal and plateau sites. The seasonal cycle of the eBC mass fraction exhibits a minimum f(eBC) ≈0.1 % in February–March and a maximum ∼4 %–5 % in August–October. Source areas were calculated using 50 d FLEXPART footprints. The highest eBC concentrations and the lowest ωo were associated with air masses coming from South America, Australia and Africa. Vertical simulations that take BC particle removal processes into account show that there would be essentially no BC particles arriving at Dome C from north of latitude 10∘ S at altitudes <1600 m. The main biomass-burning regions Africa, Australia and Brazil are more to the south, and their smoke plumes have been observed at higher altitudes than that, so they can get transported to Antarctica. The seasonal cycle of BC emissions from wildfires and agricultural burning and other fires in South America, Africa and Australia was calculated from data downloaded from the Global Fire Emissions Database (GFED). The maximum total emissions were in August–September, but the peak of monthly average eBC concentrations is observed 2–3 months later in November, not only at Dome C, but also at the SPO and the coastal stations. The air-mass residence-time-weighted BC emissions from South America are approximately an order of magnitude larger than from Africa and Oceania, suggesting that South American BC emissions are the largest contributors to eBC at Dome C. At Dome C the maximum and minimum scattering coefficients were observed in austral summer and winter, respectively. At the SPO σsp was similar to that observed at Dome C in the austral summer, but there was a large difference in winter, suggesting that in winter the SPO is more influenced by sea-spray emissions than Dome C. The seasonal cycles of σsp at Dome C and at the SPO were compared with the seasonal cycles of secondary and primary marine aerosol emissions. The σsp measured at the SPO correlated much better with the sea-spray aerosol emission fluxes in the Southern Ocean than σsp at Dome C. The seasonal cycles of biogenic secondary aerosols were estimated from monthly average phytoplankton biomass concentrations obtained from the Cloud-Aerosol Lidar with Orthogonal Polarization (CALIOP) satellite sensor data. The analysis suggests that a large fraction of the biogenic scattering aerosol observed at Dome C has been formed in the polar zone, but it may take a month for the aerosol to be formed, be grown and get transported from the sea level to Dome C.